The Influence of Cultural And Christianity ValuesToward The Society - Luther Tarigan; Pestaria Naibaho; Togap Siringo (Conference Series, 2020)
This study aims to krlow the improvcrrant of civilization end Christianity values, As the impact of Dr. I.L. Nommensen content of teaching towards the society at Huta Dame as the fast village at Tarutung, Indore s ia. Metlnd of research was descriptive qualitative with the sample of 85 informants, similar with 20 % from 428 populatkin. Data gathering was by depth-interview that was put in tix data display and tix resuk was tahn lated and administered quantâatively which derived from primer data. It was found that there was a significant influence of civilization and Christianity values towards society around wéhin contribution 53.96 & and tfe other rest 46.03%, were impacted by otlx r variables. It implies that civilization and Christianity values are two importam segwnt that play a main role in nurturing t c society. Both c ivilization arid Christianity values have strong function to educate and characterize the society for art sides of life.